Ética na formação do pedagogo - PAIXÃO, Ananda Samanta Melo da (2020)
Thinking about the philosophy of education and ethics in human formation, especially the pedagogue, led me to the main research problem, namely: How does the ethical formation of the pedagogue take place? From this problem I thought the following questions: What is the importance of ethics in human formation these days? How can ethics contribute to educator / teacher education? What difficulties do emerge in the process of construction of the pedagogue in Brazil? How is ethics reflected and studied in education, especially in the Pedagogy course of the Federal University of Pará? Understanding ethics in the formation of the pedagogue is the general objective to be achieved in this study whose specific objectives are: a) To understand the importance of ethics in human formation in the present day; b) To verify how ethics can contribute to the formation of the educator / pedagogue; c) To understand the difficulties that emerge in the process of construction of the pedagogue in Brazil. d) Analyze how ethics is studied in education, especially in the course of Pedagogy of UFPA. The methodology was developed through bibliographical and documentary studies. The most important historical sources were books by authors such as Rios (1997), Soares (2000) and Vázques (1995), as well as articles by Antônio Joaquim Severino published especially in National Periodicals from 1974 to 2016 and his lattes, through which it was possible to verify their intellectual production on ethics, the Curricular Project of the Pedagogy Course and the interviews carried out with the students of pedagogy. It was concluded that the subjects involved with the philosophy of education allied with ethics, are concerned with the ethical-political formation of educators and question the variables that determine the profile of this professional. However, although there is no specific discipline of ethics in the undergraduate course in Pedagogy of the UFPA, Belém Campus, many graduates are able to perceive at some point in their formation references to this subject, even if this occurs only in some disciplines such as for example, philosophy of education.